CLINICAL AUDIT OF FOETOMATERNAL OUTCOME IN PREGNANCIES WITH FIBROID UTERUS - Sarwar, Iram; Habib, Sadia; Bibi, Attiya; Malik, Naushaba; Parveen, Zahida (Journal of Ayub Medical College Abbottabad, 2012)
Background: Leiomyoma, myoma, leiomyoma or fibroids are synonymous terms. They may be present in as many as 1 in 5 women over age 35 years. If pregnancy is associated with fibroids, it leads to multiple complications. Objectives of this study were to evaluate the maternal and foetal outcome in women having pregnancy with fibroids in uterus and the complications associated with fibroids during the pregnancy. Methods: This descriptive study was conducted in the Department of Obstetrics and Gynaecology, Ayub Teaching Hospital Abbottabad from March 2009 to March 2010. Data were collected on performa regarding demographic variables, obstetrical history, mode of delivery, maternal outcome, maternal complications, and foetal outcome. Mean and standard deviation was calculated for age, period of gestation, and obstetrical history. Frequency and percentages was calculated for booking status, maternal outcome, maternal complications and foetal outcome. Results: Thirty patients were included in this study who had pregnancy with fibroid. Normal delivery was achieved in 14 (46.66%) patients. Eight (26.67%) patients had caesarean section and eight (26.67%) had miscarriages. Seven (23.33%) patients had no complications while 8 (26.67%) had miscarriages, 8 (26.67%) had postpartum haemorrhage, 10 (33.33%) had preterm delivery, and 3 patients had ante-partum haemorrhage. Two (10%) patients had premature rupture off membranes and 1 patient (3.33%) had pain abdomen and technical difficulty during caesarean section. There were 12 (40%) healthy babies. Five (16.67%) babies delivered with morbidity but recovered. There were 4 (13.33%) intrauterine deaths and one early neonatal death. Conclusion: Fibroid in pregnancy, especially multiple intramural fibroids and fibroids larger than 10 Cm, cause miscarriage and preterm labour. Keywords: Leiomyoma, myoma, fibroid, maternal complication, foetal outcome